3D bioprinting for bile duct tissue engineering: current status and prospects - Gao, Bo (Frontiers in Bioengineering and Biotechnology, 2025)
Bile duct disorders, including cholangiocarcinoma, primary sclerosing cholangitis, and iatrogenic injuries, pose significant clinical challenges due to limited regenerative capacity and the complexity of the biliary tree. In recent years, 3D bioprinting has emerged as a promising approach for bile duct tissue engineering by providing patient-specific geometries and facilitating the spatial organization of cells, scaffolding materials, and bioactive factors. This review presents a comprehensive overview of 3D bioprinting techniques for bile duct tissue engineering, focusing on fundamental principles, biomaterial selection, current achievements, key challenges, and future perspectives. We systematically discuss the latest technological breakthroughs, highlight emerging innovations such as organoid-based strategies and microfluidic-assisted 3D printing, and evaluate the prospects for clinical translation. Finally, we outline the main challenges—such as biocompatibility of materials, vascularization, immunological barriers, standardization of protocols, and regulatory hurdles—and propose directions for future research, emphasizing multidisciplinary collaboration and translational studies.